VD_FINDINFO HC / 2013 / 317 vom 29. April 2013 - VD Tribunal cantonal (2013)
OBLIGATION D'ENTRETIEN, ENFANT, MAJORITÉ{ÂGE}, DROIT DE GARDE, AUTORITÉ PARENTALE, ACTION EN MODIFICATION | 134 al. 1 CC, 134 CC, 277 al. 2 CC, 279 CC, 286 CC